Nuclear Security Education at Pakistan Institute of Engineering and Applied Sciences (PIEAS): Current Status, Future Prospects and the Lessons Learnt - Tariq Majeed Dr. (International Journal of Nuclear Security, 2016)
In this paper, the details of nuclear security education at Pakistan Institute of Engineering and Applied Sciences (PIEAS) have been discussed. Nuclear Security education was initiated at PIEAS as a sub-specialty of its MS Nuclear Engineering Program in October 2009. Two courses, Nuclear Security (NE-581) and Physical Protection Systems (NE-582) have been offered on regular basis in the 3rd and 4th semesters. To date, 72 students have been graduated with this sub-specialty. The most important lesson learnt is that introduction of nuclear security related courses in nuclear engineering program has opened up new venues of applications of nuclear engineering principles in the area of nuclear security. It is also helping in the development of nuclear security culture among the nuclear engineering professionals working inside the nuclear facilities. PIEAS has maintained a close collaboration with all stakeholders at national level to facilitate the development of human resource in the area of nuclear security. PIEAS has also extended its full cooperation with International Atomic Energy Agency (IAEA) for the development of nuclear security educational network, such as INSEN (International Nuclear Security Education Network), and NSSC (Nuclear Security Support Centers) Network. PIEAS will continue its long journey of imparting effective nuclear security education by introducing more nuclear security related courses, initiating faculty development programs and developing required nuclear security education related infrastructure in the form of laboratories in the future.
Keywords: nuclear security; education; training; security culture; nuclear engineering; INSEN; NSSC